THE EFFECT OF PRODUCT QUALITY AND PRICE ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE: A STUDY AT CV. MUTIARA TIMUR - Aden Akbar G; Muh Abdul Aziz; Muhammad Khairul Amal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effects of product quality and price on customer loyalty with customer satisfaction as a mediating variable at CV Mutiara Timur, a light steel distributor in Sukabumi. The increasing competition in the construction material industry requires companies to understand the key factors that influence customer satisfaction and loyalty in order to maintain long-term business sustainability. This research employed a quantitative approach using a survey method with questionnaires distributed to customers of CV Mutiara Timur. The data were analyzed using Structural Equation Modeling (SEM) with the AMOS software. The results indicate that product quality and price have positive and significant effects on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty. Product quality is also found to have a positive and significant direct effect on customer loyalty. However, price does not have a significant direct effect on customer loyalty, although it influences loyalty indirectly through customer satisfaction. These findings confirm the important role of customer satisfaction as a mediating variable in strengthening the relationship between product quality, price, and customer loyalty. This study concludes that improving product quality and implementing fair and competitive pricing strategies are essential to enhance customer satisfaction and foster long-term customer loyalty. The findings provide practical implications for managers in the construction material industry to design effective marketing strategies focused on customer satisfaction and loyalty development